A new species of Propimelodus Lundberg & Parisi, 2002 Siluriformes: Pimelodidae from rio Araguaia, Mato Grosso, Brazil - Rocha, Marcelo Salles; Oliveira, Renildo Ribeiro de; Py-daniel, Lúcia Rapp (Neotropical Ichthyology, 2007)
A new species of Propimelodus from the middle course of the rio Araguaia is described. Propimelodus araguayae, new species, can be distinguished from its congeners in having a conspicuous black dot on the base of the dorsal-fin rays (vs. a different pattern), large eyes (29.7-34.8% of head length and 62.7-74.7% of snout length vs. 14.5-21.1% and 31-44% in P. caesius and 9.5-19.7% and 17-38% in P. eigenmanni), anal-fin lobe present (vs. absent), premaxillary bone with three irregular rows of teeth (vs. 4-5 in P. caesius and 5-8 in P. eigenmanni), tip of anterior lateral process of basipterygium at the same level as the tip of the anterior medial process (vs. anterior lateral process extending beyond the tip of the anterior medial process), total number of vertebrae (43-44 vs. 47-48 in P. caesius and 45-46 in P. eigenmanni) and total number of gill rakers (28-33 vs. 20-23 in P. caesius and 19-20 in P. eigenmanni). This new species is possibly endemic to the middle course of the rio Araguaia. Copyright © 2007 Sociedade Brasileira de Ictiologia.
Keywords: Pimelodidae; Siluriformes